(untitled) (The South Asianist Journal, 2013)
As Aya Ikegame points out at the very start of her book, princely states formed almost half the land area of British India, yet the Rajas who ruled those states ‘have been entirely neglected’; they are ‘truly the people without history,’ she says, ‘ghosts of the past... occasionally amusing eccentric[s]... whose role historians are little inclined to address’ (p. 1). Her new book is a major step in redressing that neglect.